The Diversity Amphibian (Order Anura) on Diefferent Habitat Types in Balik Bukit Resort Bukit Barisan Selatan National Park - Roly Mardinata; Gunardi Djoko Winarno; Nuning Nurcahyani (Jurnal Sylva Lestari, 2018)
Balik Bukit Resort Bukit Barisan Selatan National Park (BBSNP) is a protected area where various amphibians habitat. The conditions and quality of habitat, of course determines the diversity of amphibians. This study aimed to analyze the diversity to detect that theamphibians (order Anura), comparing the diversity of amphibians (order Anura) based on different types of habitat and identifying amphibian habitat conditions (order Anura) in Resort Balik Bukit of Bukit Barisan Selatan National Park. This study uses three replications in each habitat type (primary forest, bush and swamp) and using Visual Encounter Surveys in amphibian biodiversity data retrieval. The data have been analyzed using the Shannon Wiener index, and community similarity index by calculating the evenness. Research shows that the value of diversity is still classified as being on the three types of habitat with the highest diversity found in primary forest habitat that habitat conditions in Resort Behind the hill is still ensure the growth and proliferation of amphibians order Anura. Keywords: Anura, Amphibians, Environmental Indicators, Resort Balik Bukit TNBBS